The Effect Of Employee Welfare And Career Development On Turnover Intention In Manufacturing Companies - Lis Nurdiana; Miftah Nurasyhari (DEAL: International Journal of Economics and Business, 2024)
Employee welfare has an important role in reducing turnover intention in manufacturing companies. Met physical, psychological, and social needs create job satisfaction that increases employee loyalty. Factors such as an inclusive work environment, technical training, and work-life balance contribute significantly to employee retention. On the other hand, career development that is less relevant or not integrated often fails to reduce turnover intention. An effective career development program requires a holistic approach with the integration of talent management strategies. Research shows that mediating factors such as job satisfaction strengthen the relationship between well-being or career development and turnover intention. These findings encourage companies to design more comprehensive programs to lower turnover and increase productivity.